Computer Simulation Development of Hydro-cyclone Performance in Solid Liquid Separation - Su Rat, Santie Chai Khamkeo (IRC, 2020)
The separation of particle and fluid using device called hydro-cyclone has been widely adapted in various industry especially oil and gas field. The solids mainly the sand flow out from the well with the oil need to be separated out before the oil can be flown to the production facility as sand can corrode the equipment and lead to higher cost consumption for the production. In oil field, the produced crude from the well may vary in the properties especially the density and the viscosity. The two properties are among the properties that will influent the separation performance of the hydro-cyclone. However, significant of the relation between these parameters to the separation efficiency is unclear and to investigate it experimentally will be expensive and time consuming.